Role of nuclear factor κB in multiple sclerosis and experimental autoimmune encephalomyelitis - Yuan Yue; Sarrabeth Stone; Wensheng Lin (Neural Regeneration Research, 2018)
The transcription factor nuclear factor κB (NF-κB) plays major roles in inflammatory diseases through regulation of inflammation and cell viability. Multiple sclerosis (MS) is a chronic inflammatory demyelinating and neurodegenerative disease of the central nervous system (CNS). It has been shown that NF-κB is activated in multiple cell types in the CNS of MS patients, including T cells, microglia/macrophages, astrocytes, oligodendrocytes, and neurons. Interestingly, data from animal model studies, particularly studies of experimental autoimmune encephalomyelitis, have suggested that NF-κB activation in these individual cell types has distinct effects on the development of MS. In this review, we will cover the current literature on NF-κB and the evidence for its role in the development of MS and its animal model experimental autoimmune encephalomyelitis.